2016
DOI: 10.1093/cid/ciw543
|View full text |Cite
|
Sign up to set email alerts
|

Macracanthorhynchus ingensInfection in an 18-Month-Old Child in Florida: A Case Report and Review of Acanthocephaliasis in Humans

Abstract: A case of acanthocephaliasis in an 18-month-old child caused by Macracanthorhynchus ingens is reported from Florida. This represents only the third documented case of this species in a human host. An overview of human cases of acanthocephaliasis in the literature is presented, along with a review of the biology, clinical manifestations and pathology in the human host, morphology, and diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Acanthocephala (thorny-headed worms) are endoparasites of jaw-bearing vertebrates (Gnathostomata) including humans [1][2][3][4]. In their digestive tract, the worms usually grow to adults of several millimeters to a few centimeters in length, followed by heterosexual reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Acanthocephala (thorny-headed worms) are endoparasites of jaw-bearing vertebrates (Gnathostomata) including humans [1][2][3][4]. In their digestive tract, the worms usually grow to adults of several millimeters to a few centimeters in length, followed by heterosexual reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Moniliformis moniliformis prevalence within the population of wild rats was low but similar to studies reported from Spain (Galán- Puchades et al., 2018), Malaysia (Mohd Zain et al., 2012) and Jamaica (Waugh et al., 2006). Human infection results from the ingestion of infected insects and sporadic cases of human infections have been reported from Florida (Mathison et al., 2016), Nigeria (Ikeh et al., 1992), Saudi Arabia (Sahar et al., 2010) and Iran (Maraghi et al., 2014). To date, human infections with M. moniliformis have not been reported in the Caribbean region.…”
Section: Discussionmentioning
confidence: 99%
“…Taenia haeruca Pallas, 1776 Echinorhynchus gigas Bloch, 1782 Geographic distribution. Worldwide (Mathison et al 2016).…”
Section: Macracanthorhynchus Hirudinaceus (Pallas 1781)mentioning
confidence: 99%
“…Definitive hosts are pigs; dogs and other mammals can serve as reservoir hosts. Zoonotic in humans ( Mathison et al 2016 ).…”
Section: Checklist Of Eukaryotic Human Parasitesmentioning
confidence: 99%
See 1 more Smart Citation